Impact of triple bottom line reporting on accounting information disclosure of some selected money deposit banks in Nigeria (Journal of Economic Research & Business Administration, 2021)
The practice of only financial accounting-based reporting in the past is regarded as socially andenvironmentally unfriendly. This study, therefore, examines the impact of triple bottom line-based reportingon the accounting information disclosure of some selected money deposit banks in Nigeria. Thisstudy employed a survey research design. A sample of 300 staff of the selected banks were purposivelyselected from study population of eight selected banks in Nigeria. Primary data was collected throughthe questionnaire to elicit data from the respondents. The data collected was analyzed using correlationanalysis, analysis of variances (ANOVA) and multiple regression models using SPSS version 20. Thestudy found that the P-value of 0.00 < 0.01. Thus, TBL reporting has a positive effect on accountinginformation disclosure of banks in Nigeria. This study concluded that the activities of banks have movedbeyond reporting only financial accounting information at the expense of accounting for social and environmentaleffects of these banks on the communities where they operate in Nigeria. This study recommendsthat the accountants should be financially motivated to acquire adequate knowledge on how toaccount for social and environmental activates of their companies.Key words: accounting information disclosure, banks, triple bottom-line.